Web Services Strategy - SAP Platform it's not your father's SAP. - Campbell, Scott
Packaged business applications have dominated enterprise IT landscapes for over a decade. Now these products are undergoing major changes to segway into the world of Web Services. SAP has been one of the most aggressive companies in embracing this revolution. Its NetWeaver platform is an ambitious suite of integration technologies designed to morph SAP into enterprise SOAs. SAP unveiled a four-year roadmap for NetWeaver in 2003. This article looks at the platform at its halfway point as well as SAP's vision for creating a Web Services-based agile business process infrastructure.